Spectrophotometric analyses of strong acid and metal-ion precipitated humic acid from the Santa Barbara groundwater - Laride, William Albaracin (Miagao, Iloilo University of the Philippines Visayas, 2010)
Humic acid from the Santa Barbara groundwater was precipitated using strong acid and six selected metal ions, Fe(III), Cr(III), Ni(II), CU(II), Cd(II) and Pb(II). Solutions containing humic acid and metal ions at various concentration ratios were prepared and the UV-Vis absorbance was measured. Humic acid precipitate and metal-humate salts were also subjected to FT-IR analyses.The UV-Vis of HA solutions at different concentrations gave a featureless curve with highest absorbance recorded in the UV region. The absorbance of the solution also decreases with decreasing concentration of humic acid. The presence of metal ions significantly increases the UV-Vis absorbance of humic acid. The same as also true for the absorbance of the metal ions in the presence of humic acid. It is not evident in the UV-Vis spectra of the HA-metal ionspossible formation of HA-metal complexes ; The FT-IR spectra of humic acid precipitated by treatment with a strong acid show the characteristic peaks of carboxyl, hydroxyl, alkene, aromatic, carbonyl, phenol and polysaccharide functional groups. The spectra CR(III), Fe(III), Ni(II) and Cu(II) humate salts confirmed the formation of metal-humate complexes through the oxygen atoms of both the carbonyl and carboxylic acid functional groups. This is indicated by the reduction of the COO symmetric stretching to lower wavelength from 1712 cm-1 to 1600 cm-1 and the appearance of the COO antisymmetric stretching at 1400 cm-1. IR spectra of the humate salts of PB(II) and Cd(II) also indicated formation of metal-humate complexeshowever coordination is only limited to the carboxyl functional group as indicated by the absorption band of the carbonyl oxygen, C=O, which were not present in the spectra of Cr(III), Fe(III), Ni(II) and Cu(II).
Special Problem (M. in Chemistry) -- Miagao, Iloilo : U.P. Visayas, February 2010.